The Acute and Delayed Effects of Vagal Nerve Stimulation on an Absence Epilepsy Model in WAG/Rij - Uyar, Ramazan; Turk, Cezmi Cagri; Isik, Nejat; Kalelioglu, Mufit; Onat, Filiz; Ozek, Memet (TURKISH NEUROSURGICAL SOC, 2016)
AIM: Vagal nerve stimulation (VNS) is an effective method of treatment for epilepsy patients either unresponsive to medical therapy or not suitable for resective surgeries. We designed an experimental study on Wistar Albino Glaxo rats from Rijswijk (WAG\textbackslash{}Rij) to investigate the effects of VNS on a non-convulsive epilepsy model. MATERIAL and METHODS: The experiment was performed on six WAG/Rij rats, a validated strain for genetic absence seizures. The animals were underwent VNS and the effects were investigated on electroencephalography (EEG) recordings at 22, 24, 26 hours of stimulation and 15 days after the cessation, for duration of spike and wave complexes (SWC), the numbers, mean duration of SWC and frequencies in an hour. RESULTS: EEG recordings demonstrated that the mean duration of SWC was 353.1 seconds and the number of activity per hour was 62 at the baseline. There were statistically significant decreases in the total duration of SWC and the number of activities (61.8\% and 78\% decrease, respectively). There were no significant decreases in the mean duration of SWC and the frequencies. CONCLUSION: The acute stimulation of the vagal nerve caused a statistically significant decrease both in overall duration of SWC and the number of complexes in an hour. Moreover, the positive effects seemed to last even 15 days after the cessation of the stimulation. Further studies focusing on different stimulation parameters and delayed effects of the VNS on human absence seizures are warranted.
Keywords: Absence; Animal model; Epilepsy; Vagal nerve stimulation; WAG/Rij rat